Kontribusi Kekuatan Lengan, Kelentukan Dan Keseimbangan Terhadap Kemampuan Roll Ke Depan Pada Senam Lantai Siswa SMKN I Makassar - Ichsani Ichsani; Sulaeman Sulaeman; Andi Yulianti (UNIVERSITAS NEGERI MAKASSSAR, 2021)
The purpose of this study was to determine the contribution of arm strength, flexibility and balance to the forward roll ability of the students of SMK Negeri 1 Makassar. This type of research is a quantitative descriptive study. The sample in this study were students of SMK Negeri 1 Makassar who were selected through random sampling technique. The results of the regression analysis of arm strength on the forward roll ability in floor exercise contributed 36%. The results of the flexibility regression analysis on the forward roll ability of the students of SMKN I Makassar contributed 48.50%. The results of the balance regression analysis on the ability to roll forward on the floor gymnastics of SMKN I Makassar students contributed 26.50%. And the results of the regression analysis of arm strength, flexibility, and balance on the ability to roll forward on the floor gymnastics students of SMKN I Makassar contributed 57.50%..